Ensuring participatory based decision-making practice in higher education through E-management: a faculty initiative - Hashim, F.; Alam, G.M.; Siraj, Saedah (2009)
One of the challenges faced by any organization is ensuring acceptable and reliable decision making processes. Though many organizations have developed their own approaches to address these issues not many have used technology to ensure effective participatory based decision making. This paper argues for and presents a model that incorporates reliable participatory based decision making practices and quality management indicators through strategic use of technology. The e-management system is an initiative of a faculty in a higher institution of learning. The paper describes and assesses a model called QuESt (Quality E-management System). QuESt integrates web-based technologies into an interconnected system to enable decision making by all stakeholders at multi levels of responsibility. Discussion is first focused on the bureaucracy and participatory models of decision making, then moves on to the research context, description of QuESt and discussion of the features and functions of the system. The paper concludes with an assessment of the potentialities of the system in taking an organisation's internal and external processes to the next level using technology to ensure evidence based decision making, to interconnect staff roles and responsibilities and to use feedback to take appropriate action.